Water quantity and quality under future climate and societal scenarios: a basin-wide approach applied to the Sorraia river, Portugal - Almeida, Carina (2018)
Water resources are impacted by several stressors like over-population and over consumption that compromises their availability. These stressors are expected to progressively intensify due to climate change in most regions of the world, with direct impact on watersheds and river systems. This study investigates the effect of different watershed pressure scenarios due to climate change in the hydrological regime of the Sorraia River basin, Portugal. This catchment includes one of the largest irrigated areas in the country, thus being strongly influenced by anthropogenic activities, associated to hydrological (irrigation, flow regulation, damming) and nutrient stressors. The SoilWater Assessment Tool has been used to simulate water flow and nutrient dynamics in the watershed while considering inputs from two climate models and three societal scenarios. Results have shown that the predicted rainfall reductions will have a significant impact on river flow and nutrient concentrations when compared to baseline conditions. River flow will expectably decrease by 75%, while nitrogen and phosphorus concentrations in river water will expectably increase by 500% and 200%, respectively. These differences are more evident for storylines that consider increasing pressures such as population growth and agricultural expansion marked with unsustainable practices and increased reliance on technology. The results of this study indicate a possible future outcome and provide effective guidelines for the formulation of water management policies to counter the impacts of climate change and corresponding environmental pressures in the Sorraia River basin